The Psychological Effects of Parentification in Girls within Single-Parent Families - Shamsaee, Majid; Hossienimajd , Hannaneh Sadat; Parsa Brojeni, Aghdas; Ghanad Tousi, Dorri; Ghasemzadeh, Azizreza (Psychology of Woman Journal, 2024)
Objective: Parentification, the process whereby children assume roles and responsibilities typically associated with those of a parent, has been identified as a phenomenon with significant psychological implications, particularly within single-parent families. This study aims to explore the psychological effects of parentification on girls living in single-parent households, focusing on their emotional, social, academic, and personal development. Methods and Materials: Employing a qualitative research design, this study collected data through semi-structured interviews with 21 girls aged 13 to 18, who were identified as assuming adult roles within their single-parent families. Theoretical saturation was achieved to ensure a comprehensive understanding of the phenomenon. Data analysis followed a thematic approach, allowing for the identification of key themes related to the psychological effects of parentification. Findings: The findings reveal that parentification leads to both positive and negative psychological effects. Positively, it fosters emotional maturity, resilience, and independence. Negatively, it imposes an emotional burden, results in social isolation, and poses challenges to academic performance. Importantly, the presence of social support was identified as a crucial factor in mitigating some of the adverse effects of parentification. Conclusion: The study concludes that parentification has a profound impact on the psychological well-being of girls in single-parent families, with significant implications for their emotional, social, and academic development. While parentification can promote certain developmental strengths, it also necessitates the need for targeted interventions to support parentified children and mitigate the challenges they face.